Examining the Effect of Consuming C8 Medium-Chain Triglyceride Oil for 14 Days on Markers of NLRP3 Activation in Healthy Humans. (6th April 2022) - Neudorf, Helena; Jackson, Garett; Little, Jonathan P.
Abstract : Chronic, low-grade inflammation is associated with the development of numerous diseases and is mediated in part by overactivation of the NLRP3 inflammasome. The ketone body beta-hydroxybutyrate ( β HB) suppresses the NLRP3 inflammasome and alters intracellular signalling pathways in vitro and in animal models; however, this effect has not yet been shown in vivo in humans. The purpose of this single-arm pilot trial was to determine if consuming 15 mL of C8 medium-chain triglyceride (trioctanoin; MCT) oil, which induces mild elevation of β HB, twice daily (30 mL total) for 14 days would suppress markers of NLRP3 inflammasome activation in young, healthy humans while following their habitual diet. Consuming a single dose of 15 mL of C8 MCT oil significantly raised blood β HB from fasting at 60 minutes and 120 minutes post ingestion (both P < 0.05 ). However, consumption of C8 MCT oil for 14 days did not impact markers of monocyte NLRP3 inflammasome activation compared to baseline. Specifically, caspase-1 activation and secretion of its downstream product interleukin (IL)-1 β were unchanged following 14 days of C8 MCT oil supplementation when measured in unstimulated and LPS-stimulated whole blood cultures (all P > 0.05 ). Acetylation of histone H3 on the lysine residue 9 was unchanged (P < 0.05 ) and acetylation of lysine residue 14 was decreased (P < 0.05 ) following 14 days of supplementation. Thus, adding twice daily C8 MCT oil supplementation to the habitual diet of young, healthy humans does not appear to suppress NLRP3 inflammasome activation.